The conceptual framework of quantum field theory - Duncan, Anthony (Professor of physics) (Oxford : Oxford University Press, 2012)
This text provides a step by step construction of the framework of relativistic quantum field theory, starting from a minimal set of basic foundational postulates. The emphasis is on a careful and detailed description of the conceptual subtleties of modern field theory.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Quantum field theory